Serenoa repens, lycopene and selenium versus tamsulosin for the treatment of LUTS/BPH. An Italian multicenter double‐blinded randomized study between single or combination therapy (PROCOMB trial). Issue 15 (23rd August 2014) - Morgia, Giuseppe; Russo, Giorgio I.; Voce, Salvatore; Palmieri, Fabiano; Gentile, Marcello; Giannantoni, Antonella; Blefari, Franco; Carini, Marco; Minervini, Andrea; Ginepri, Andrea; Salvia, Giuseppe; Vespasiani, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Phytotherapy has been used to treat patients with lower urinary tract symptoms (LUTS). We evaluated the efficacy and tolerability of combination therapy between Serenoa Repens (SeR), Lycopene (Ly), and Selenium (Se) + tamsulosin versus single therapies. METHODS PROCOMB trial (ISRCTN78639965) was a randomized double‐blinded, double‐dummy multicenter study of 225 patients between 55 and 80 years old, PSA ≤ 4 ng/ml, IPSS ≥12, prostate volume ≤60 cc, Qmax ≤15 ml/sec, postvoid residual urine (PVR) <150 ml. Participants were randomized group A (SeR‐Se‐Ly), group B (tamsulosin 0.4 mg), group C (SeR‐Se‐Ly + tamsulosin 0.4 mg). The primary endpoints of the study were the reduction of IPSS, PVR, and increase of Qmax in group C versus monotherapy groups. RESULTS The decrease for combination therapy was significantly greater versus group A (P < 0.05) and group B (P < 0.01) for IPSS and versus group A (P < 0.01) for PVR from baseline to 6 months. A greater decrease in IPSS was observed for Group C versus group A (P < 0.01) and increase in Qmax versus group B (P < 0.01), from 6 months to 12 months. At one year, the changes of IPSS and Qmax were greater for Group C versus monotherapies (each comparison <0.05). The proportions of men with a decrease of at least three points (each comparison P < 0.05) and decrease of 25% for IPSS (each comparison P < 0.01) were greater for Group C. CONCLUSION SeR‐Se‐Ly + tamsulosin therapy is more effective than single therapies in improving IPSS and increasing Qmax in patients with LUTS. Prostate 74:1471–1480, 2014. © 2014 Wiley Periodicals, Inc.